Responsible tourism : (CAB International, 2012)
Tourism is one of the world's biggest industries. Responsible tourism is concerned with the effects of tourism on people, ecology, and communities, and seeks to ameliorate these impacts by providing tourism that benefits host communities, improves working conditions, involves the local community, promotes cultural heritage, and benefits the environment. This book discusses responsible tourism as a whole, including the politics, policy and planning behind it, and the major subject sub-topics, such as poverty reduction, the environment, transport, governance, wildlife tours and heritage.